(untitled) (Sebha University Conference Proceedings, 2022)
Maghreb countries - Algeria, Tunisia, and Libya have joined the United Nations Convention against Corruption (UNCAC). This convention obliges its member states to submit periodic reports on the extent of their implementation and their commitment to the provisions contained in the prevention and control of corruption. On one hand; the reports provide an opportunity to review and demonstrate areas of success and failures. On the other hand, the reports help in identifying the challenges and difficulties faced by these states in adapting their legal system to the provisions of the United Nations Convention against Corruption. This study demonstrates several aspects of the country review process, particularly the review of first cycle implementation, which targets chapters III and V. The paper further focuses on legal and institutional anti-corruption framework and explains protection measures for witnesses, experts and whistle-blowers in cases of reporting corruption. It also clarifies the most recent developments after the presentation of the national reports of Maghreb countries.